2000
DOI: 10.1142/s0218194000000328
|View full text |Cite
|
Sign up to set email alerts
|

Production and Maintenance of Goal-Oriented Software Measurement Models

Abstract: Production and maintenance of measurement models are crucial in the context of an advanced software development organization. The paper suggests a goal-oriented measurement model life cycle that, starting out from the high-level organizational goals, drives software organizations towards a structured process to deal with measurement models. The life cycle results into an integrated component of the management activities pointed to generate, refine, and fulfill the organizational goals, whereas the final measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2002
2002
2007
2007

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 2 publications
0
17
0
Order By: Relevance
“…3 presents the method we apply for obtaining valid and useful metrics. This method is based on the methods proposed by [12] and the MMLC (Measure Model Life Cycle [13]). In this figure continuous lines show metric flow and dotted lines show information flow.…”
Section: Methods For Defining Metricsmentioning
confidence: 99%
“…3 presents the method we apply for obtaining valid and useful metrics. This method is based on the methods proposed by [12] and the MMLC (Measure Model Life Cycle [13]). In this figure continuous lines show metric flow and dotted lines show information flow.…”
Section: Methods For Defining Metricsmentioning
confidence: 99%
“…The proposal of measures is of no value if their practical use is not shown empirically (Basili et al 1999;Kitchenham et al 1995;Schneidewind 1992;Cantone and Donzelli 2000). Hence, our main motivation was to investigate, through experimentation, whether the measures we proposed for UML class diagram structural complexity and size could be good predictors of two class diagram characteristics that are related to maintainability: understandability and modifiability.…”
Section: Objectives Of This Researchmentioning
confidence: 99%
“…Several reviews of the most up-to-date empirical studies related to OO measures (Basili et al 1999;Kitchenham et al 1995;Schneidewind 1992;Cantone and Donzelli 2000;Briand and Wüst 2002) have shown that the dependent variables that are investigated most frequently are fault-proneness (probability of fault detection), the number of faults or changes in a class, the effort of various development activities, and expert opinion about the psychological complexity of a class.…”
Section: Related Workmentioning
confidence: 99%
“…The Soft Goal Modelling aims at producing the operational definitions of the soft goals that emerged during the organisational modelling, sufficient to capture and make explicit the semantics that are usually assigned implicitly by the involved agents [8,9,10] and to highlight the system quality issues from the start. A soft goal is refined in terms of subordinate soft goals, hard goals, tasks and constraints.…”
Section: Figure 1 -The Requirements Engineering Frameworkmentioning
confidence: 99%